In-flight simulators and fly-by-wire/light demonstrators : a historical account of international aeronautical research - Hamel, Peter G.; Jategaonkar, Ravindra V. (Springer, 2017)
This book offers the first complete account of more than sixty years of international research on In-Flight Simulation and related development of electronic and electro-optic flight control system technologies ("Fly-by-Wire" and "Fly-by-Light"). They have provided a versatile and experimental procedure that is of particular importance for verification, optimization, and evaluation of flying qualities and flight safety of manned or unmanned aircraft systems. Extensive coverage is given in the book to both fundamental information related to flight testing and state-of-the-art advances in the design and implementation of electronic and electro-optic flight control systems, which have made In-Flight Simulation possible. Written by experts, the respective chapters clearly show the interdependence between various aeronautical disciplines and in-flight simulation methods. Taken together, they form a truly multidisciplinary book that addresses the needs of not just flight test engineers, but also other aeronautical scientists, engineers and project managers and historians as well. Students with a general interest in aeronautics as well as researchers in countries with growing aeronautical ambitions will also find the book useful. The omission of mathematical equations and in-depth theoretical discussions in favor of fresh discussions on innovative experiments, together with the inclusion of anecdotes and fascinating photos, make this book not only an enjoyable read, but also an important incentive to future research. The book, translated from the German by Ravindra Jategaonkar, is an extended and revised English edition of the book Fliegende Simulatoren und Technologieträger, edited by Peter Hamel and published by Appelhans in 2014.